Doing Women's Film History : Reframing Cinemas, Past and Future - Gledhill, Christine; Knight, Julia (Book collections on Project MUSE., 2015)
"Distinguished scholars Christina Gledhill and Julia Knight's anthology shows women's work in and around cinema across time in different parts of the world, from pioneering days, through recent developments, pointing towards future modes of production and history writing. At the same time, given the very different historical, socioeconomic, political, and cultural conditions of the cinemas in view, these essays concentrate on key historiographic questions. They include how to identify women's participation in their cinema cultures, where to locate previously unconsidered sources of evidence, how to develop new research methodologies and analytical concepts capable of revealing the impact of gender on film production and reception, and how to reframe film history to accommodate such questions and approaches. If what unifies the range of essays consists of their central focus on women and gender, thereby decentralizing American cinema in film history, it is not the intention to fragment cinemas into discrete national boxes. Instead, analysis of different geopolitical and historical circumstances of women's involvement in different cinemas enable us to better understand the complexity and diversity of that involvement and therefore of cinema itself"--